Advances in managing rare acquired bleeding disorders. Issue 6 (2nd June 2020) - Franchini, Massimo; Marano, Giuseppe; Cruciani, Mario; Mengoli, Carlo; Pati, Ilaria; Masiello, Francesca; Veropalumbo, Eva; Pupella, Simonetta; Vaglio, Stefania; Liumbruno, Giancarlo Maria
ABSTRACT: Introduction: Rare acquired bleeding disorders include a wide spectrum of coagulopathies characterized by spontaneous or post-trauma and post-surgery hemorrhages in patients without a previous personal or family history of bleeding. Areas covered: This review, based on a Medline/PubMed search during the last 20 years, will focus mainly on rare acquired bleeding disorders caused by autoantibodies against coagulation factors, including autoantibodies against factor VIII (acquired hemophilia A), von Willebrand factor (acquired von Willebrand syndrome) and other coagulation factors (factors V, X, XI, and XIII). The pathogenic, laboratory, and clinical features of these rare hemorrhagic conditions will be discussed, with particular attention to their management. Expert opinion: The treatment of rare acquired bleeding disorders includes the control of bleeding and the elimination of the autoantibody and of the underlying disease, when present. As the bleeding clinical phenotype is often severe, the management of affected patients is particularly challenging. Thus, while an early diagnosis of the acquired coagulopathy is essential to start the most appropriate treatment and to improve patients' outcomes, the support of specialized centers is equally important to provide a correct management of such complicated cases.